A review on application and heat transfer enhancement of supercritical CO2 in low-grade heat conversion - Zhang, Shijie; Xu, Xiaoxiao; Liu, Chao; Dang, Chaobin (Applied energy, 2020)
•The experimental tests on supercritical CO2 power cycle are briefly reviewed.•The heat transfer mechanisms present the principles for heat transfer optimization;•The various approaches of heat transfer enhancement are reviewed and discussed;•Buoyancy criteria provide guidance for the selection of enhancement approaches. Trans-critical CO2 Rankine system is a new technology for low-grade heat utilization which has high energy conversion efficiency and exergo-economic efficiency. The gas heater is one of the most important components in trans-critical CO2 Rankine system, which is a crucial challenge for its practical application because of high pressure and abrupt change in thermo-physical properties of supercritical CO2.The aim of this paper is to provide basic background knowledge on trans-critical CO2 Rankine cycle in low-grade heat conversion and present a review of experimental tests and demonstrations on supercritical CO2 operation considering heat-to-power systems. Since the heat transfer criteria and enhancement of supercritical CO2 is vital for its application in the real-scale compact heat exchanger design and system operation, this review further discusses the turbulent convective heat transfer and its enhancement approaches of supercritical CO2 in heating system. A comprehensive summary of the heat transfer mechanisms and criteria as well as their derivation and evaluation methods is conducted to provide some references for the system operation, heat exchanger design and heat transfer enhancement. Some of the shortcomings of the existing research are pointed out. Based on the above discussion, this review presents the basic ideas and approaches of heat transfer enhancement and discus the application of heat transfer criteria in heat transfer enhancements. Finally, the authors bring forward the way of latter researching of supercritical heat transfer and enhanced measures.